Associação entre consumo alimentar e atividade física com a síndrome metabólica em mulheres na pós-menopausa - Carvalho, Christiane Nogueira de Medeiros (2013)
Post-menopause is characterized as the period beginning one year after the permanent cessation of menstrual cycles, which is typically related to medical disorders that, in association with Metabolic Syndrome (MS), represent a set of cardiovascular risk factors. Objective: To assess dietary intake and the prevalence of metabolic syndrome in postmenopausal women, according to the level of physical activity. Methods: The sample consisted of 82 women, evaluated in the Northern Zone of the city of Natal / RN who were participants in the Natal Active Program. People completed a Food Frequency Consumption Questionnaire (FFCQ) and were interviewed about physical activity. Anthropometric measurements and biochemical tests were used to diagnose MS (Metabolic Syndrome). Result: The active women consumed more protective foods (flaxseed, nuts, whole wheat bread, brown rice and olive oil) than inactive women. Risky foods (sugar, crackers, white bread, white rice, margarine and beef) were consumed more by the group of inactive women. The prevalence of MS was higher in inactive women (53.30%) than in physically active women (46.70%). Conclusion: Active post-menopausal women had a higher daily intake of protective foods in relation to cardiovascular disease, while the inactive post-menopausal women had higher intake of risky foods for such diseases